Bioadhesives for internal medical applications: A review. (1st July 2018) - Zhu, Wenzhen; Chuah, Yon Jin; Wang, Dong-An
Graphical abstract: Abstract: Bioadhesives such as tissue adhesives, hemostatic agents, and tissue sealants have gained increasing popularity in different areas of clinical operations during the last three decades. Bioadhesives can be categorized into internal and external ones according to their application conditions. External bioadhesives are generally applied in topical medications such as wound closure and epidermal grafting. Internal bioadhesives are mainly used in intracorporal conditions with direct contact to internal environment including tissues, organs and body fluids, such as chronic organ leak repair and bleeding complication reduction. This review focuses on internal bioadhesives that, in contrast with external bioadhesives, emphasize much more on biocompatibility and adhesive ability to wet surfaces rather than on gluing time and intensity. The crosslinking mechanisms of present internal bioadhesives can be generally classified as follows: 1) chemical conjugation between reactive groups; 2) free radical polymerization by light or redox initiation; 3) biological or biochemical coupling with specificity; and 4) biomimetic adhesion inspired from natural phenomena. In this review, bioadhesive products of each class are summarized and discussed by comparing their designs, features, and applications as well as their prospects for future development. Statement of Significance: Despite the emergence of numerous novel bioadhesive formulations in recent years, thus far, the classification of internal and external bioadhesives has not been well defined and universally acknowledged. Many of the formulations have been proposed for treatment of several diseases even though they are not applicable for such conditions. This is because of the lack of a systematic standard or evaluation protocol during the development of a new adhesive product. In this review, the definition of internal and external bioadhesives is given for the first time, and with a focus on internal bioadhesives, the criteria of an ideal internal bioadhesive are adequately discussed; this is followed by the review of recently developed internal bioadhesives based on different gluing mechanisms.